Unpacking the Role of Advanced Growth Mindset in Fostering Multicultural Awareness Among University Students - Fawziah Zahrawati B; Nursaptini; Siswantoyo (SocioEdu: Sociological Education, 2026)
This study addresses the growing need for multicultural awareness in higher education within increasingly diverse and pluralistic societies. Although the growth mindset has been widely examined in relation to academic resilience and achievement, its contribution to multicultural awareness remains underexplored. This research investigates how an advanced growth mindset supports the development of multicultural awareness among university students. Using a qualitative design, the study involved 11 students from the Social Studies Education Program at IAIN Parepare, selected through purposive sampling. Data were collected through in-depth semi-structured interviews, participant observation, and analysis of reflective documents, and were analyzed using thematic analysis. The findings identify five interconnected dimensions: intrinsic growth motivation, cognitive reframing of differences, self-regulated communication, cultural sensitivity in practice, and experiential multicultural learning. Students perceived cultural differences as opportunities for reflection rather than conflict, demonstrating adaptive and dialogical engagement. The study concludes that an advanced growth mindset functions as a psychological mediator, transforming cross-cultural challenges into reflective learning experiences. These findings imply the need to integrate reflective and cross-cultural collaborative learning into higher education curricula and are significant in bridging growth mindset theory with multicultural education to foster resilient and socially responsible graduates.